Alternative agents versus prophylactic platelet transfusion for preventing bleeding in patients with haematological disorders after chemotherapy or stem cell transplantation (Protocol). - Estcourt, L; Gregg, R; Stanworth, S; Doree, C; Trivella, M; Murphy, M; Tinmouth, A (John Wiley and Sons, Ltd, 2014)
This is the protocol for a review and there is no abstract. The objectives are as follows: To determine whether alternative agents (e.g. artificial platelet substitutes, platelet-poor plasma, fibrinogen, rFVIIa, thrombopoietin mimetics) are as effective and safe as the use of platelet transfusions for the prevention of bleeding (prophylactic platelet transfusion) in patients with haematological disorders who are undergoing myelosuppressive chemotherapy or stem cell transplantation. Anti-fibrinolytics (lysine analogues) will not be included in this review because they have been the focus of another Cochrane review (Wardrop 2013).